Ductile Fracture Prediction in Mg-ZM51M Alloy Using Inverse-Calibrated Damage Models - Thamer Sami Alhalaybeh; Ashiq Iqbal Chowdhury; Hammad Akhtar; Yanshan Lou (Metals, 2025)
Magnesium (Mg) alloys are gaining widespread use in the automotive and construction industries for their potential to enhance performance and lower manufacturing costs, making them ideal for lightweight structural applications. However, despite these advantages, extruding Mg alloys remains technically challenging due to their inherently limited formability and the strong crystallographic textures that form during deformation. This study aimed to comprehensively characterize the ductile fracture behavior of ZM51M Mg alloy round bars under various stress states and to improve the reliability of ductile failure predictions through the application and calibration of multiple uncoupled damage criteria. Tensile and compressive tests were conducted on specimens of varying geometries (dogbone, notched R5, shear, uniaxial compression, and plane strain compression specimens) and dimensions, meticulously cut along the extrusion direction of the round bar. These tests encompassed a wide spectrum of stress–strain responses and fracture characteristics, including uniaxial tension, uniaxial compression, and shear-dominated states. An inverse analysis approach, involving iterative numerical simulation coupled with experimental data, was employed to precisely determine fracture strains from the test results. The plastic deformation behavior was accurately modeled using the combined Swift–Voce hardening law. Subsequently, three prominent uncoupled ductile fracture criteria—Rice–Tracey, DF2014, and DF2016—were calibrated against the experimental data. The DF2016 criterion demonstrated superior predictive accuracy, consistently yielding the most accurate fracture strain predictions and significantly outperforming the Rice–Tracey and DF2014 criteria across the tested stress states. The findings of this work provide significant insights for improving the assessment of formability and fracture prediction in Mg alloys. This research directly contributes to overcoming the challenges associated with their inherent formability limitations and complex deformation textures, thereby facilitating more reliable design and broader adoption of Mg alloys in advanced lightweight structural solutions.